An Update on Laboratory Diagnosis of Liver Inherited Diseases. (8th October 2013) - Zarrilli, Federica; Elce, Ausilia; Scorza, Manuela; Giordano, Sonia; Amato, Felice; Castaldo, Giuseppe
Abstract : Liver inherited diseases are a group of genetically determined clinical entities that appear with an early chronic liver involvement. They include Wilson's disease (hepatolenticular degeneration), hereditary hemochromatosis, and alpha-1-antitrypsin deficiency. In addition, cystic fibrosis, although it is not specifically a liver disease, may cause a severe liver involvement in a significant percentage of cases. For all these pathologies, the disease gene is known, and molecular analysis may contribute to the unequivocal diagnosis. This approach could avoid the patient invasive procedures and limit complications associated with a delay in diagnosis. We review liver inherited diseases on the basis of the genetic defect, focusing on the contribution of molecular analysis in the multistep diagnostic workup.